Transreligiosity and Religious Revitalization in Modern Greece: Bridging Religion and Science through Geomythology - Evgenia Fotiou (Religions, 2023)
This article examines the revitalization of the ancient Greek religion in modern Greece and the way some of its adherents approach mythology. This religious movement challenges the dominant religious discourse in modern Greece by claiming legitimacy through indigeneity, while making important arguments regarding the perceived spiritual and value crisis in their culture. At a time that right-wing extremisms and fundamentalisms are rising globally, this religious movement places emphasis on worldview and imagines a kind of citizen who engages with universal ideals while maintaining a strong connection to a unique ethnic identity. At the same time, Ethnikoi Hellenes challenge prevailing understandings of religion by making ‘logos’ or reason central to their theology. Thus, they challenge the association of Indigenous religions with “irrationality”, while pointing out the inconsistencies and irrationalities of monotheistic religions, which they consider responsible for the widespread “cultural” crisis facing humanity. The example of one group’s engagement with geomythology has been used to demonstrate that they do not conceive religion and science as contradictory but complementary, thus exhibiting transreligiosity.